Attachment security is associated with the experience of specific positive emotions in middle childhood. Issue 5 (2nd September 2020) - Obeldobel, Carli A.; Kerns, Kathryn A.
ABSTRACT: Adaptive emotion expression characterizes secure parent-child relationships in which children rely on attachment figures for secure base and safe haven support. We hypothesized that more securely attached children would report experiencing greater positive emotion. Children (N=92; M=11.91 years) completed the Friends and Family Interview which was coded for attachment security indicators (narrative coherence, mother and father safe haven support, mother and father secure base support). We analyzed Youth Values in Action Inventory strengths that reflected positive emotions (curiosity, zest, hope, love, gratitude). No attachment security indicators correlated with curiosity, all correlated with zest and gratitude, and four correlated with hope and love. Controlling for IQ, age, and temperament, attachment security significantly predicted positive emotion (12-19% variance); father secure base support uniquely predicted positive emotion. Our findings highlight the important role parental attachment plays in children's emotion experience and have implications for explaining why attachment might relate to children's other close relationships.